Unmanned Aerial Vehicle Mapping for Improving Spatial Accuracy in Rural Settlement Planning - Endah Tisnawati; Luhur Sapto Pamungkas; Endang Setyowati; Adwitya Baskara (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2026)
Accurate spatial documentation is essential for rural settlement planning, particularly in hilly areas where conventional field surveys are time‑consuming and often lack detailed topographic information. This study aims to evaluate the effectiveness of Unmanned Aerial Vehicle (UAV) mapping in improving spatial data accuracy and survey efficiency for settlement planning. The research was conducted in Puspo Hamlet, Purworejo, a rural settlement located in a complex hilly landscape with slopes of 15–35°. An exploratory case study approach based on spatial analysis was applied, integrating UAV aerial surveys, field observations, and photogrammetric processing using Structure‑from‑Motion techniques. The UAV survey covered approximately 35 hectares and produced high‑resolution orthophotos with a ground sampling distance of 3–5 cm/pixel as well as DEM and DSM datasets with horizontal accuracy of ±10 cm and vertical accuracy of ±15 cm. The results show that UAV mapping provides highly detailed spatial information while reducing survey time to about two days compared with more than one week using conventional survey methods.